2005
DOI: 10.1084/jem.20041918
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of astroglial nuclear factor κB reduces inflammation and improves functional recovery after spinal cord injury

Abstract: In the central nervous system (CNS), the transcription factor nuclear factor (NF)-κB is a key regulator of inflammation and secondary injury processes. After trauma or disease, the expression of NF-κB–dependent genes is highly activated, leading to both protective and detrimental effects on CNS recovery. We demonstrate that selective inactivation of astroglial NF-κB in transgenic mice expressing a dominant negative (dn) form of the inhibitor of κBα under the control of an astrocyte-specific promoter (glial fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
479
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 520 publications
(510 citation statements)
references
References 61 publications
28
479
0
3
Order By: Relevance
“…In particular, pioglitazone administration prevented the induction of pro-inflammatory IL-1beta, IL-6 and MCP-1, compared to vehicle-treated controls or animals pre-treated with PPAR-gamma antagonist GW9662 (59). Knockout mice lacking pro-inflammatory genes such as ICAM1 and NF-kappaB show decreased neuronal loss after SCI (58). Similarly, in adult rats treated with TZDs, post-SCI induction of ICAM1 and NF-kappaB was significantly curtailed (59).…”
Section: Ppar-gamma Ligands Induce Neuroprotection After Spinal Cord mentioning
confidence: 94%
“…In particular, pioglitazone administration prevented the induction of pro-inflammatory IL-1beta, IL-6 and MCP-1, compared to vehicle-treated controls or animals pre-treated with PPAR-gamma antagonist GW9662 (59). Knockout mice lacking pro-inflammatory genes such as ICAM1 and NF-kappaB show decreased neuronal loss after SCI (58). Similarly, in adult rats treated with TZDs, post-SCI induction of ICAM1 and NF-kappaB was significantly curtailed (59).…”
Section: Ppar-gamma Ligands Induce Neuroprotection After Spinal Cord mentioning
confidence: 94%
“…Although activation of NF-kB in neurons is often protective, its activation in microglia tends to promote neuronal apoptosis, perhaps due to the production of proinflammatory cytokines, reactive oxygen species (ROS) and excitotoxins (John et al, 2003;Mattson and Meffert, 2006). Supporting the idea that NF-kB's well-documented role in inflammation can foster central nervous system (CNS) injury following trauma, targeted inhibition of NF-kB in astroglial cells by tissue-specific expression of the IkBa super-repressor noticeably ameliorated recovery of mice following spinal cord injury and this effect coincided with a reduced production of proinflammatory cytokines (Brambilla et al, 2005). Recently, increased levels of NF-kB have been shown to be associated with K þ loss and cortical neuron apoptosis following serum withdrawal and to correlate with elevated levels of the proapoptotic alternatively spliced product of the bcl-x gene, Bcl-xS (Tao et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Consistent with this assumption, reactive astrocytes in vitro do produce neurotoxic molecules such as NO, reactive oxygen species and TNFa. Bethea and colleagues have also shown that inhibiting NF-κB expression in astrocytes was sufficient to promote increased neuronal survival following mechanical injury [12]. Furthermore, activated myelin-specific T cells reduce astrocytic expression of GLAST, one of the two primary glutamate transporters used by astrocytes to buffer and protect CNS neurons from exposure to high glutamate levels [62].…”
Section: Adjuvants Cytokines and The Subsequent Consequences Of Astrmentioning
confidence: 99%
“…Recent data clearly refutes this view. For example, NF-κB is an inducible transcription factor that initiates the subsequent expression of several inflammatory molecules [12,13]. Several studies now indicate that neuronal expression of NF-κB is induced by a variety of insults, including TNF and mechanical injury and that this neuronal induction is associated with subsequent neuronal expression of inducible nitric oxide synthase (INOS) and superoxide dismutase (SOD) [14][15][16][17].…”
Section: Neurons As Inflammatory Response Cells?mentioning
confidence: 99%